2019
DOI: 10.1177/2055102919871638
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sensory-processing sensitivity and sense of coherence on depressive symptoms in university students

Abstract: Sensory-processing sensitivity differentiates individuals according to responsivity to internal and external stimuli. It has been positively correlated with depressive symptoms. Meanwhile, sense of coherence, an individual’s perception that stressors are comprehensible, manageable, and meaningful for their life, could improve depression. This cross-sectional study investigated the moderation effect of sense of coherence on the relationship between sensory-processing sensitivity and depressive symptoms in unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
0
15
0
10
Order By: Relevance
“…There are two main reasons to consider a participant's level of SPS in the context of an LST program: (a) SPS could predict various health-related indices, and (b) SPS could indicate individual differences in the beneficial effects from psychological interventions. Many studies have revealed that SPS is correlated with mental health concerns, such as stress (Benham, 2006), depression (Liss, Timmel, Baxley, & Killingsworth, 2005;Yano, Kase, & Oishi, 2019;Yano & Oishi, 2018), and affectivity (Acevedo et al, 2014;Jagiellowicz, Aron, & Aron, 2016). Additionally, SPS has been shown to moderate the beneficial effects from psychological interventions.…”
Section: Sensory Processing Sensitivity In the Context Of Lstmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two main reasons to consider a participant's level of SPS in the context of an LST program: (a) SPS could predict various health-related indices, and (b) SPS could indicate individual differences in the beneficial effects from psychological interventions. Many studies have revealed that SPS is correlated with mental health concerns, such as stress (Benham, 2006), depression (Liss, Timmel, Baxley, & Killingsworth, 2005;Yano, Kase, & Oishi, 2019;Yano & Oishi, 2018), and affectivity (Acevedo et al, 2014;Jagiellowicz, Aron, & Aron, 2016). Additionally, SPS has been shown to moderate the beneficial effects from psychological interventions.…”
Section: Sensory Processing Sensitivity In the Context Of Lstmentioning
confidence: 99%
“…These findings suggest that the types of approaches effective for improving mental health differ according to individual differences in SPS levels; that is, the best choice of which life skills to focus on when constructing an LST program may differ between high-and low-SPS individuals. However, since most studies have focused on high-SPS individuals (Bakker & Moulding, 2012;Brindle, Moulding, Bakker, & Nedeljkovic, 2015;Yano et al, 2019;Yano & Oishi, 2018), further studies should pay attention to low-SPS individuals and provide the findings for reducing their depressive tendency levels (Greven et al, 2019;Lionetti et al, 2018).…”
Section: Sensory Processing Sensitivity In the Context Of Lstmentioning
confidence: 99%
“…However, few studies [13] have examined how university students cope with these types of stressful conditions by focusing on their stress resistance during the COVID-19 pandemic. In this study, we measured sense of coherence (SOC), the potential of which has been theoretically indicated [14] and empirically tested during normal periods [14,15,16] to investigate the stress resistance of university students and their ability to maintain their mental health status. Antonovsky, who conceptualized SOC [17] de ned SOC as "a global orientation that expresses the extent to which one has a pervasive, enduring though dynamic feeling of con dence that (1) the stimuli deriving from one's internal and external environments in the course of living are structured, predictable and explicable; (2) the resources are available to one to meet the demands posed by the stimuli; and (3) these demands are challenges, worthy of investment and engagement" [18].…”
Section: Introductionmentioning
confidence: 99%
“…Other possibilities are more theoretical. One study examining the relationship between SPS, Sense of Coherence (SOC), and depression confirmed that SOC coordinates the relationship between SPS and depression (Yano et al, 2019); however, there are few approaches to increasing SOC, and it is not realistic to expect individuals with high SPS to raise SOC for their mental health. Life Skills Training, however, may be a practical approach, and according to a study that investigated the relationship between SPS, Life Skills Training, and depression, specific life skills such as emotional coping modulated the relationship between SPS and depression; even if SPS was high, better life skills resulted in significantly lower scores for depression (Yano et al, 2020).…”
Section: Efficacious Techniques For Regulating Mental Health Conditiomentioning
confidence: 99%